Drying of Pomegranate Arils and Selection of a Suitable Drying Model - Doymaz, Ibrahim (SPRINGER, 2011)
The drying characteristics of pomegranate arils were investigated in temperature range of 50-70 degrees C. The increase in drying air temperature resulted in a decrease in drying time. The drying rate was found to increase with temperature, thereby reducing the total drying time. Thirteen drying models were evaluated in the kinetics research. The goodness of fit of the proposed models was evaluated by using the determination of coefficient (R-2), mean relative percent error (P), reduced chi-square (chi(2)), and root means square error (RMSE). The Midilli et al. model showed a better fit to experimental drying data as compared to other models. Effective moisture diffusivity (D-eff) ranged from 9.447 x 10(-11) to 3.481 x 10(-10) m(2)/s as calculated by the Fick's second law of diffusion. The temperature dependence of the value of effective moisture diffusivity followed an Arrhenius-type relationship. The activation energy for the moisture diffusion was determined to be 60.34 kJ/mol.
Keywords: Pomegranate arils; Air drying; Effective moisture diffusivity; Activation energy; KINETICS; GRAPE; Food Science & Technology